Chemotherapy adherence is a favorable prognostic factor for elderly patients with multiple myeloma who are treated with a frontline bortezomib-containing regimen - Cho, Hee-Jeong; Seo, Sang-Kyung; Baek, Dong Won; Park, Sung-Woo; Lee, Yoo-Jin; Sohn, Sang-Kyun; Lee, Ho-Sup; Lee, Won Sik; Lee, Ji Hyun; Kim, Sung Hyun; Moon, Joon-Ho (Journal of yeungnam medical science, 2018)
Elderly patients with multiple myeloma (MM) are vulnerable to adverse events (AEs). This study evaluated adherence to chemotherapy and treatment outcomes in elderly patients treated with a frontline bortezomib (BTZ), melphalan, and prednisone (VMP) regimen and regimens without BTZ.BackgroundElderly patients with multiple myeloma (MM) are vulnerable to adverse events (AEs). This study evaluated adherence to chemotherapy and treatment outcomes in elderly patients treated with a frontline bortezomib (BTZ), melphalan, and prednisone (VMP) regimen and regimens without BTZ.One-hundred and forty elderly patients who were diagnosed with MM from March 2007 to March 2015 were included in this retrospective study. To evaluate regimen adherence, patients who were treated with more than 4 cycles were assigned to the good adherence group.MethodsOne-hundred and forty elderly patients who were diagnosed with MM from March 2007 to March 2015 were included in this retrospective study. To evaluate regimen adherence, patients who were treated with more than 4 cycles were assigned to the good adherence group.Among the 140 patients, 71 were treated with a frontline VMP and 69 with non-BTZ regimens. The median age was 71 years (range, 65-90 years). The VMP group showed a higher complete response rate than the non-BTZ group: 26.8% vs. 7.2%. More patients in the VMP group achieved ≥very good partial response (VGPR) and ≥PR. In the VMP group, 27 patients (38.0%) received less than 4 cycles. The VMP good adherence group showed a higher 3-year overall survival (OS) rate (70.9%) than the poor adherence group (60.2%, p=0.059). In the multivariate analysis, treatment with ≥4 cycles of VMP was a favorable factor for OS.ResultsAmong the 140 patients, 71 were treated with a frontline VMP and 69 with non-BTZ regimens. The median age was 71 years (range, 65-90 years). The VMP group showed a higher complete response rate than the non-BTZ group: 26.8% vs. 7.2%. More patients in the VMP group achieved ≥very good partial response (VGPR) and ≥PR. In the VMP group, 27 patients (38.0%) received less than 4 cycles. The VMP good adherence group showed a higher 3-year overall survival (OS) rate (70.9%) than the poor adherence group (60.2%, p=0.059). In the multivariate analysis, treatment with ≥4 cycles of VMP was a favorable factor for OS.A good adherence to a frontline VMP regimen resulted in favorable long-term survival. Adequate management of AEs will be needed to achieve favorable outcomes in elderly patients with MM.ConclusionA good adherence to a frontline VMP regimen resulted in favorable long-term survival. Adequate management of AEs will be needed to achieve favorable outcomes in elderly patients with MM.